The Effectiveness of Prone Position Respiratory Rehabilitation Covid-19 Patients; Literature Review - Ike Adelia; Zainal Abidin; Anggia Astuti (STIKes Kepanjen, 2022)
Introduction: Coronavirus Disease 2019 (Covid-19) which can cause pulmonary complications,cardiovascular, and muscular which results in various organ dysfunctions which in turn can reduce the patient's lung functional capacity. This matter can cause a decrease in the patient's oxygen saturation (SpO2), causing hypoxaemia due to inadequate ventilation and perfusion diffusion leading to sepsis to septic shock. For this, various efforts to increase oxygen saturation deficit and decrease mortality, including by means of respiratory rehabilitation in a position prone. Method: This method uses a literature review design by using 3 databases, namely Google Scholar, Science Direct, Pubmed. Result: The results of this literature review using breathing exercises are: prone position. The time span of 10 journals that have been reviewed using average duration of implementation is 2-4 hours per day, with 1-4 times per session scheduled for 4 weeks. A given patient's lung functional capacity x prone position intervention in 10 journals increased, in results it shows that it is statistically significant in increasing Oxygen saturation SpO2 (p < 0.005). Conclution: These results indicate an effective prone position in improving oxygenation.